ANALISIS PENGARUH KEPUASAN KERJA SEBAGAI MEDIASI DALAM HUBUNGAN ANTARA KEPEMIMPINAN TRANSFORMASIONAL DAN KOMPENSASI TERHADAP KINERJA ( Studi Pada Dosen Politeknik Negeri Semarang ) - Teguh Budi Santosa, 11.4202.0014 (Students Journal of Accounting and Banking, 2013)
This study aims to analyze the effect of transformational leadership and compensation toward lecturer performance with job satisfaction as a mediated variables at Politeknik Negeri Semarang. The respondent of this study all of the lecturer who worked at Politeknik Negeri Semarang as a public civil servant in 5 department : Department of Mechanical Engineering, Department of Civil Engineering, Department of Electrical Engineering, Department of Accounting and Business Administration Programs, which amount 352 lecturer and the research used proportional random samling technique method. Sample of this research is amount 105 lecturer. To analyse the research instrument used validity test with factor analysis, and reliability test with alpha cronbach, and multiple linier regression, and t statistics to prove the research hypothesis and test of mediated effect. The result prove that transformational leadership and compensation have positive and significance impact to job satisfaction, transformational leadership, compensation and job satisfaction have positive and significance impact to lecturer performance. The result of this research is indicated that the influence of transformational leadership and compensation toward lecturer performance not mediated by job satisfaction Â Keywords : transformational leadership, compensation, job satisfaction and lecturer performance